2013
DOI: 10.1248/cpb.c13-00493
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Novel Benzo-Fused Heteroaryl Derivatives as Ca<sup>2+</sup>/Calmodulin-Dependent Protein Kinase II Inhibitors

Abstract: Based on the structure activity relationship of 2-(4-phenoxybenzoyl)-5-hydroxyindole (1), a novel structural class of Ca 2 /calmodulin-dependent protein kinase II (CaMKII) inhibitors were synthesized. We show in this study that the acidic proton at the N(1)-position of the indole moiety is not essential for CaMKII inhibitory activity. Among the synthesized compounds, we found the benzofuran and benzothiazole derivative as promising scaffolds for the developement of potent CaMKII inhibitors. In particular, comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
0
8
0
1
Order By: Relevance
“…[1][2][3] Among these structures, 2-aroylbenzothiazoles have attracted signicant attention owing to their pharmaceutical and medicinal applications. [4][5][6] Accordingly, several methods have been investigated for the synthesis of 2-aroylbenzothiazoles, including (i) transitional metalcatalyzed sp 2 C-H bond functionalization of benzothiazoles, and (ii) cyclization with or without sulfuration of orthosubstituted anilines. Some examples could be listed, as Feng and Song previously reported a copper-catalyzed acylation of benzothiazoles with aryl methyl ketones to afford 2-aroylbenzothiazoles.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Among these structures, 2-aroylbenzothiazoles have attracted signicant attention owing to their pharmaceutical and medicinal applications. [4][5][6] Accordingly, several methods have been investigated for the synthesis of 2-aroylbenzothiazoles, including (i) transitional metalcatalyzed sp 2 C-H bond functionalization of benzothiazoles, and (ii) cyclization with or without sulfuration of orthosubstituted anilines. Some examples could be listed, as Feng and Song previously reported a copper-catalyzed acylation of benzothiazoles with aryl methyl ketones to afford 2-aroylbenzothiazoles.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, as shown in Figure 1 , 6-hydroxybenzothiophene ketone A exhibits potential for the treatment of breast cancer, endometriotic tissues, and other diseases by functioning as an inhibitor of 17b-hydroxysteroid dehydrogenase Type 1 (17b-HSD1) [ 12 , 13 , 14 ]. C2-arylacylated benzothiazole B act as a novel structural class of Ca 2+ /calmodulin-dependent protein kinase II (CaMKII) inhibitors with the potential to be developed as anti-inflammatory agents [ 15 ]; 2-Benzothiazolyl-phenylmethanone C were found to be potent fatty acid amide hydrolase (FAAH) inhibitors with beneficial effects for disorders such as pain and inflammation [ 16 ]. As a potent inhibitor of antiapoptotic Bcl-2 proteins, acylpyrogallol D inhibited growth and induced apoptosis in human breast and prostate cancer cell lines [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some benzothiazoles can be used as labeling reagents to aid in the diagnosis of Alzheimer's disease (AD) at an early-to-moderate stage and to monitor the efficiency of treatment. 2 In addition, other studies have revealed that several benzothiazoles can serve as promising scaffolds for potent CaMKII 3 and 17-HSD1…”
mentioning
confidence: 99%